Positive influence of being overweight/obese on long term survival in patients hospitalised due to acute heart failure - Littnerova, Simona; Parenica, Jiri; Spinar, Jindrich; Vitovec, Jirí; Linhart, Ales; Widimsky, Petr; Jarkovsky, Jiri; Miklik, Roman; Spinarova, Lenka; Zeman, Kamil; Belohlavek, Jan; Malek, Filip; et al. (PloS one, 2015)
BACKGROUND: Obesity is clearly associated with increased morbidity and mortality rates. However, in patients with acute heart failure (AHF), an increased BMI could represent a protective marker. Studies evaluating the "obesity paradox" on a large cohort with long-term follow-up are lacking. METHODS: Using the AHEAD database (a Czech multi-centre database of patients hospitalised due to AHF), 5057 patients were evaluated; patients with a BMI <18.5 kg/m2 were excluded. All-cause mortality was compared between groups with a BMI of 18.5-25 kg/m2 and with BMI >25 kg/m2. Data were adjusted by a propensity score for 11 parameters. RESULTS: In the balanced groups, the difference in 30-day mortality was not significant. The long-term mortality of patients with normal weight was higher than for those who were overweight/obese (HR, 1.36; 95% CI, 1.26-1.48; p<0.001)). In the balanced dataset, the pattern was similar (1.22; 1.09-1.39; p<0.001). A similar result was found in the balanced dataset of a subgroup of patients with de novo AHF (1.30; 1.11-1.52; p = 0.001), but only a trend in a balanced dataset of patients with acute decompensated heart failure. CONCLUSION: These data suggest significantly lower long-term mortality in overweight/obese patients with AHF. The results suggest that at present there is no evidence for weight reduction in overweight/obese patients with heart failure, and emphasize the importance of prevention of cardiac cachexia.
Keywords: proporcionální rizikové modely; analýza přežití; Male; kohortové studie; Overweight; srdeční selhání; Obesity; Cohort Studies; Databases, Factual; následné studie; hospitalizace; Proportional Hazards Models; obezita; databáze faktografické; Aged; mužské pohlaví; senioři; nadváha; Survival Analysis; Follow-Up Studies; akutní nemoc; Acute Disease; lidé; ženské pohlaví; Heart Failure; Humans; Body Mass Index; Hospitalization; index tělesné hmotnosti; Female; lidé středního věku; Middle Aged